Cover Picture: Azaphthalocyanines: Red Fluorescent Probes for Cations (Chem. Eur. J. 16/2013). Issue 16 (8th April 2013) - Novakova, Veronika; Lochman, Lukáš; Zajícová, Ivana; Kopecky, Kamil; Miletin, Miroslav; Lang, Kamil; Kirakci, Kaplan; Zimcik, Petr
<x xml:space="preserve">Abstract</x> The concept of sensing metal cations by using fluorescence changes in non‐aggregating AzaPc molecules that exhibit significant intramolecular charge transfer (ICT) in the OFF state was demonstrated by binding Na+ and K+ to an aza[15]crown‐5 recognition moiety. It is important to note that this concept works not only in organic solvents, but also in water after the sensor molecules are incorporated into silica nanoparticles. For more details see the Communication by V. Novakova, P. Zimcik et al. on page 5025 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>